The Relationship between Restless Leg Syndrome Severity with Neuropsychological Performance and Menstrual Disorders in Young Women - Afsaneh Bahrami; Masoumeh Askari; Zahra Rajabi; Zahra Sadat Hoseini; Gordon Ferns (Mashhad University of Medical Sciences, 2023)
Background & aim: Restless leg syndrome (RLS) is a frequent sensory dyskinesia disorder of the nervous system and a cause of disability in several aspects. This study aimed to determine the relationship between RLS and mood complications, menstrual patterns, and its associated symptoms among young women.Methods: This cross-sectional study was undertaken on 118 female university students in Birjand, Iran, from December 2019 to January 2020 using a multistage cluster sampling method. The degree of RLS was assessed using the International RLS Severity Scale. The severity of PMS was characterized via the Premenstrual Syndrome Screening Tool (PSST). Neuropsychological performance of participants was evaluated. Data analysis was performed by SPSS software (version 16.0).Results: Of 118 participants, 29.7%, 32.2%, 27.9%, and 10.2% of them were not affected by RLS or suffered from mild, moderate, or severe types of RLS, respectively. The subjects with RLS had a significantly lower duration of their menstruation cycle and higher PSST scores compared to those without it. Subjects with different severities of RLS scored higher for the severity of depression, anxiety, stress, insomnia, and sleepiness than normal women (P<0.01). The RLS score was a significant factor related to the scores for cognitive abilities (β=-0.33; P=0.022), depression (β=0.32; P=0.001), anxiety (β=0.24; P=0.003), stress (β=0.44; P<0.001), quality of life (β=-0.23; P<0.001), insomnia (β=0.21; P=0.001), sleepiness (β=0.15; P=0.014) and PSST (β=0.28; P=0.019).Conclusion: In the absence of health management, RLS is potentially associated with depression, anxiety, sleep disruption, cognitive impairment, decreased quality of life, and menstrual problems.